Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3920/jiff2020.0069
|View full text |Cite
|
Sign up to set email alerts
|

Microbial contaminants in wild harvested and traded edible long-horned grasshopper, Ruspolia differens (Orthoptera: Tettigoniidae) in Uganda

Abstract: This study investigated the relative abundance and identity of microbial contaminants of the edible long-horned grasshopper (Ruspolia differens) harvested from the wild and traded in informal markets in Uganda, to reveal high health risk points. Raw samples of whole R. differens were collected from wild vegetation, trapping sites and markets. Additionally, samples of plucked and deep-fried ready-to-eat R. differens were collected from the markets. The samples were cultured on standard media for microbial quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…1). This agrees with the ndings of Labu et al [30], who observed that bacterial and fungal counts in processed grasshoppers were generally lower than in freshly harvested (unprocessed) raw insects. Heat processing (frying) would be expected to eliminate any contaminating microorganisms in the grasshoppers.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…1). This agrees with the ndings of Labu et al [30], who observed that bacterial and fungal counts in processed grasshoppers were generally lower than in freshly harvested (unprocessed) raw insects. Heat processing (frying) would be expected to eliminate any contaminating microorganisms in the grasshoppers.…”
Section: Resultssupporting
confidence: 92%
“…The reason for this is unclear but could be related to poor housing infrastructure and general sanitation in Kampala slums compared to Masaka, which had relatively better housing and sanitation infrastructures. A related study by Labu et al [30] carried out in both localities, found the mean bacterial counts in R. differens samples from Masaka (season 1 (April-May) were signi cantly higher than those in samples from Kampala. However, there was no signi cant difference in season two (November-December), but microbial species were most diverse in wild, freshly harvested samples.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Grasshoppers could potentially get contaminated from where they originate, given that they are thought to swarm to the point of harvest from “unknown sources”, although a study by Opoke et al [ 33 ] suggests a local origin from which they aggregate and swarm upon maturity. Previous studies by Ssepuuya et al [ 16 ] and Labu et al [ 34 ] show that grasshoppers surveyed at the point of harvest already had high levels of contamination with potential human pathogens.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…In countries like Niger, Uganda, Chad, and Burkina Faso, it is prohibited among some ethnic groups to consume edible insects. The Baganda tribe in Uganda has a similar taboo where women are not allowed to consume Ruspolia differens but are allowed to catch it and prepare food for their husbands (Labu et al., 2021). Due to the theory that it would cause newborns to have cone‐shaped heads, consumption of R. differens is strictly prohibited for expecting mothers (Sengendo et al., 2021).…”
Section: Barriers Of Insect Consumptionmentioning
confidence: 99%